Effective Elastic Modulus of Structured Adhesives: From Biology to Biomimetics - Xin Wang; Di Tan; Xinyu Zhang; Yifeng Lei; Longjian Xue (Biomimetics, 2017)
Micro- and nano-hierarchical structures (lamellae, setae, branches, and spatulae) on the toe pads of many animals play key roles for generating strong but reversible adhesion for locomotion. The hierarchical structure possesses significantly reduced, effective elastic modulus (Eeff), as compared to the inherent elastic modulus (Einh) of the corresponding biological material (and therefore contributes to a better compliance with the counterpart surface). Learning from nature, three types of hierarchical structures (namely self-similar pillar structure, lamella–pillar hybrid structure, and porous structure) have been developed and investigated.